FINANCIAL SUSTAINABILITY BERBASIS BUDAYA (STUDI PADA LEMBAGA PERKREDITAN DESA DI BALI) - Wiagustini, Ni Luh Putu; Panji Sedana, Ida Bagus; Aprilia, Ni Putu Ria; Simanjuntak, Graceila Regia Margareth (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.02.TAHUN.2024, 2024)
Village Credit Institutions in Bali have a strategic role in improving the village economy, especially financing for micro, small and medium enterprises. currently facing competition from similar financial institutions operating in Bali. This research aims to analyze the influence of Cultural Capital which includes Collective Culture and Organizational Culture on Financial sustainability. The research population is Village Credit Institutions in Bali which have a healthy and fairly healthy category with a total of 1,145 units. Determining the sample size was carried out using the Slovin formula, namely 100 units, samples were taken using stratified proportional random sampling based on the number of units in districts/cities in Bali. The analysis method used is Smart-PLS, it was found that Cultural Capital which includes Collective Culture and Organizational Culture is able to increase financial sustainability.